Health system resilience in the context of forced migration: a qualitative framework analysis of Germany's crisis responses in 2015 and 2020 - Jahn, Rosa; Perplies, Clara; Rast, Eilin; Biddle, Louise; Gold, Andreas W.; Bozorgmehr, Kayvan (Social science & medicine, 2025)
Background - Health system resilience, the ability of a health system to maintain its functions under stress, has received increasing attention in recent years. Shortcomings in health system resilience are often most visible in the most vulnerable settings, including the care for asylum seekers and refugees. We therefore examined how the German health system responded to challenges and uncertainties during the large-scale immigration to Europe in 2015 and the COVID-19 pandemic in 2020. - Methods - For the present study, we applied a health system resilience framework that identifies four management capacities (collecting and integrating knowledge, responding to uncertainties, managing cross-scale dynamics, generating legitimacy) and three types of crisis responses (absorptive, adaptive, transformative). The analysis was based on 40 interviews conducted in 2015 (n = 20) and 2020 (n = 20) with individuals involved in the accommodation and healthcare provision for asylum seekers and refugees. The interviews were coded and analysed based on a deductive-inductive framework analysis approach. The results of the analysis were charted into a framework matrix to facilitate comparison of patterns across interviews. - Results - The crisis responses were hindered by fragmented coordination, limited knowledge sharing, and a lack of overarching response strategy. The crisis responses were therefore largely dependent on individual actors and their respective initiatives, mostly on local levels. A comparison of themes between the interviews in 2015 and 2020 suggest that the crisis responses were characterised by short-term adaptations rather than longer-term transformations of the health system. - Conclusions - These findings suggest that improving health system resilience requires a more comprehensive and system-wide approach to obtaining, integrating, and using knowledge; as well as more clearly defined roles, particularly regarding coordination; and overarching guidelines that can inform a coherent response strategy.
Online verfügbar 12 May 2025, Version des Artikels 5 June 2025
Gesehen am 22.10.2025